2012
DOI: 10.1021/cs200536a
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Deactivation of Au–Cu/SBA-15 Catalyst for Preferential Oxidation of CO in H2-Rich Gas

Abstract: This work aims to develop an efficient catalyst for preferential oxidation (PROX) of CO in a H 2 -rich gas and obtain a clear structure−property relationship of the catalyst. A Au/CuO/SBA-15 catalyst was designed and prepared via a nanoengineering approach in which the metallic particles of average size 3 nm located in the vicinity of CuO particles were highly dispersed on the SBA-15 support. It was found that the CuO particles could reduce the gold (Au) particle size, stabilize the Au particles, and facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 39 publications
4
54
0
1
Order By: Relevance
“…Like normal supported gold nanocatalysts, this inverse CuO x /Au nanostructure yields interfacial sites between them, which have been well accepted as the active sites [43,79,80]. The FT-IR of CO adsorption showed that CO adsorbed on Au 0 was able to react with oxygen even at temperatures as low as À110°C, suggesting that Au 0 is the main active component, while CuO x is assumed to be responsible for providing active oxygen just as those reducible oxides do [10,81].…”
Section: Identification Of Active Sitesmentioning
confidence: 87%
“…Like normal supported gold nanocatalysts, this inverse CuO x /Au nanostructure yields interfacial sites between them, which have been well accepted as the active sites [43,79,80]. The FT-IR of CO adsorption showed that CO adsorbed on Au 0 was able to react with oxygen even at temperatures as low as À110°C, suggesting that Au 0 is the main active component, while CuO x is assumed to be responsible for providing active oxygen just as those reducible oxides do [10,81].…”
Section: Identification Of Active Sitesmentioning
confidence: 87%
“…Nonetheless, it is possible that due to the introduction of new activation and adsorption sites on the catalyst samples during the catalyst reduction in H 2 at high temperatures, the particle size and charge transfer effects have compensated each other to some extent. The formation of CuO, as detected by both XRD and XPS analyses for sample reduced at 700 • C, may play a major role in stabilizing the Au particles [45]. Moreover, there are no experimental or theoretical studies that vividly describe the extent to which metal particles nucleate under high temperature pretreatment.…”
Section: Effect Of Catalyst Structure On the Catalytic Performance Ofmentioning
confidence: 99%
“…Numerous studies have searched for better catalysts, examining particle-size effects 12,15 , metal-oxide-support effects 16,17 , mixed metal oxides 15,18 and ordered mesoporous materials 19 . Bimetallic catalysts 20 , the inclusion of polyoxometallates in liquid-phase media 21 , Au-ceria nanocomposites 22 and embedded Au@CeO 2 catalysts 23 have also been examined, with limited success.…”
mentioning
confidence: 99%